Distinguishing Secondary Dengue Virus Infection From Zika Virus Infection With Previous Dengue by a Combination of 3 Simple Serological Tests. (29th July 2017) - Tsai, Wen-Yang; Youn, Han Ha; Brites, Carlos; Tsai, Jih-Jin; Tyson, Jasmine; Pedroso, Celia; Drexler, Jan Felix; Stone, Mars; Simmons, Graham; Busch, Michael P; Lanteri, Marion; Stramer, Susan L; et al.
Abstract : An algorithm is proposed to distinguish primary Zika virus (ZIKV), ZIKV with previous dengue virus (DENV), and secondary DENV infections, which is critical for understanding the epidemiology, pathogenesis, and complications of ZIKV in dengue-endemic regions. Abstract: Background: The explosive spread of Zika virus (ZIKV) and associated microcephaly present an urgent need for sensitive and specific serodiagnostic tests, particularly for pregnant women in dengue virus (DENV)–endemic regions. Recent reports of enhanced ZIKV replication by dengue-immune sera have raised concerns about the role of previous DENV infection on the risk and severity of microcephaly and other ZIKV complications. Methods: Enzyme-linked immunosorbent assays (ELISAs) based on ZIKV and DENV nonstructural protein 1 (NS1) were established to test acute, convalescent phase, and post–convalescent phase serum/plasma samples from reverse-transcription polymerase chain reaction–confirmed cases including 20 primary ZIKV, 25 ZIKV with previous DENV, 58 secondary DENV, and 16 primary DENV1 infections. Results: ZIKV-NS1 immunoglobulin M (IgM) and immunoglobulin G (IgG) ELISAs combined can detect ZIKV infection with a sensitivity of 95% and specificity of 66.7%. The ZIKV-NS1 IgG cross-reactivity by samples from secondary DENV infection cases ranged from 66.7% to 28.1% (within 1 month to 1–2 years post-illness, respectively). Addition of DENV1-NS1 IgG ELISA can distinguish primary ZIKV infection; the ratio of absorbance of ZIKV-NS1 to DENV1-NS1 IgG ELISA can distinguish ZIKV with previous DENV and secondary DENV infections with a sensitivity of 87.5% and specificity of 81.3%. These findings were supported by analysis of sequential samples. Conclusions: An algorithm for ZIKV serodiagnosis based on 3 simple ELISAs is proposed to distinguish primary ZIKV, ZIKV with previous DENV, and secondary DENV infections; this could be applied to serodiagnosis for ZIKV, serosurveillance, and monitoring ZIKV infection during pregnancy to understand the epidemiology, pathogenesis, and complications of ZIKV in dengue-endemic regions.